La invitada indiscreta de la dolarización en Ecuador: la competitividad - Falconi-Benítez, Fander; Jácome-Estrella, Hugo (Sociedad y Economía, 2002)
This paper examines the relationships between dolarization and competitivity,having as referent the process that was initiated in Ecuador since January 2000.Since the decision to dolarize entails the loss of the monetary and exchange policy, and takes away the apparent competitivity of the export sector by means of devaluation, genuine competitivity becomes one of the corner stones for thesustainability of the process. An argument is made in the sense that, because  this genuine competitivity is weak in Ecuador, negative consequences are foreseable in the future.